Musical sensivity, creativity, and sociability in the play and dance movement of Ilonggo children music education possibilities - Cartagena, Hermie F.; Guadalupe, Jocelyn T. (Quezon City College of Music, University of the Philippines Diliman, 2018)
This study provides some relevant insights on the role of dance and play in enhancing children's creativity and musical sensivity. This will also enlighten other researchers and readers on the importance of dance and play in the development of one's skills and potentials. For music teachers, this study helps improve their movement pedagogy in teaching music in the classroom. Furthermore, music teachers can utilize and incorporate movement, dance and play in music class, providing a richer and more holistic music learning experience.
Thesis (M. Music Education)--University of the Philippines Diliman
Keywords: School music -- Instruction and study -- Philippines